Statistical atlases and computational models of the heart : Multi-Sequence CMR Segmentation, CRT-EPiggy and LV Full Quantification Challenges : 10th International Workshop, STACOM 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13, 2019, Revised selected papers /: Multi-Sequence CMR Segmentation, CRT-EPiggy and LV Full Quantification Challenges : 10th International Workshop, STACOM 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13, 2019, Revised selected papers. (2020) - Unknown
No abstract available